4CPS-008 Does comorbidity affect adherence to inhalers in severe asthma patients treated with biologics?. Issue 1 (23rd March 2023) - Granda, P; Villamañán, E; Carpio, C; Sobrino, C; Laorden, D; Pérez, E; Lara, C; de Andrés, S; Escario, M; Herrero, A
Abstract : Background and Importance: Comorbidities are often associated with severe asthma including those patients treated with biologics. That often contributes to poorly controlled asthma 1, which could be related to deficient adherence to inhalers. Aim and Objectives: To evaluate proportion of non-adherence to inhalers in patients with severe asthma (SA) treated with biologics according to their comorbidity and to compare two methods to assess non-adherence. Material and Methods: Cross-sectional retrospective observational study of patients with SA recruited from the SA unit of a tertiary hospital in Madrid from June to December 2020. We registered demographic data, comorbidities and concomitant therapy for asthma. Non-adherence was defined as pharmacy refill data (PRD) <80% to the primary inhaler 2 and/or Test of Adherence to Inhalers questionnaire (TAI) result s<50 3 . Concordance was assessed by determining the Cohen's kappa statistic. Primary variable: Proportion of patients classified as not having therapeutic adherence measured by both of the following methods: PRD <80% in the previous 6 months, and TAI questionnaire: a value <50. Comorbidities considered: rhinoconjunctivitis, nasal polyposis, anxiety and depression, gastroesophageal reflux, bronchiectasis, aspirin-exacerbated respiratory disease (AERD) and allergic bronchopulmonary aspergillosis. Results: 53 patients were evaluated. Median age was 61 years (IQR 51.8-67) and 33 (61%) were women. 41(77%) had comorbidity: 25(61%), rhinoconjunctivitis, 16 (38%) nasal polyposis, 15 (36%) anxiety and depression, 7 (17%) gastroesophageal reflux, 6 (15%) bronchiectasis, 5 (12%) AERD and 1(2%) allergic bronchopulmonary aspergillosis. The highest non-adherence was detected in patients with rhinoconjunctivitis by the two methods: 50% and 55% according to TAI and PRD, respectively (k=0.022 95% CI -0.256–0.3). Agreement of both methods was low in all comorbidities; nasal polyposis: 42% vs 23% (k=-0.049 95% CI -0.421–0.519); anxiety and depression: 25% vs 32%( k=0 95% CI -0.317–0.317); gastroesophageal reflux: 8% vs 10% (k=0.364 95% CI -0.21-0.938) and AERD 17% vs 10% (k=-0.154 95% CI-0.659–0.967). Conclusion and Relevance: Our results highlight a high prevalence of non-adherence to inhalers in patients with SA and other comorbidities treated with biologics. Therefore, hospital pharmacists should focus on this patient´s adherence to inhalers, especially those with rhinoconjunctivitis, when providing pharmaceutical care to SA treated with biologics in practice. References and/or Acknowledgements: 1. J Precis Respir Med, 2019;2 :5–9. 2. Assessing adherence by combining the test of adherence to inhalers with pharmacy refill records. J Investig Allergol Clin Immunol 2021;31 :58–64. 3. Test of Adherence to Inhalers. Arch Bronconeumol 2017;53 :360–1. Conflict of Interest: No conflict of interest